Associations between Secure Residential Care and Positive Behavioral Change in Adolescent Boys and Girls. Issue 2 (3rd April 2023) - Gutterswijk, Raymond V.; Kuiper, Chris H.Z.; Harder, Annemiek T.; Bocanegra, Bruno R.; van der Horst, Frank C.P.; Prinzie, Peter
ABSTRACT: Secure residential youth care facilities try to optimize their help by offering gender-specific treatment, in an attempt to achieve positive behavioral change in adolescents. In this study, we examined behavioral change in a sample of 239 Dutch adolescents ( M age = 15.59 years, SD  = 1.36 years, 54.9% girls) in secure residential care. Pretest, posttest and follow-up measurements were carried out for behavioral problems, PTSD symptoms, emotion regulation, perceived competence and family problems. Comparisons were made between girls in gender-specific care, and girls and boys in regular care. Missing data analyses revealed the dataset contained many missing values. Analyses were performed at group level, using MANCOVA, ANCOVA's and bootstrapped planned contrast, and at case level, using the Reliable Change Index. At group level, results revealed higher effectiveness of gender-specific care for girls compared to regular care for girls, only in diminishing externalizing behavioral problems. Overall, there were more similarities than differences in the effectiveness of gender-specific versus regular help. At individual level, 0–58% of the adolescents improved during their stay in secure residential care. However, most adolescents showed no change (25–88%) or even deterioration (0–39%). These results strongly emphasize the need for alternative interventions.